A novel design for a wearable thermoelectric generator based on 3D fabric structure - Wu, Qian; Hu, Jinlian (Smart materials and structures, 2017)
A flexible and wearable thermoelectric generator (TEG) could enable the conversion of human body heat into electrical power, which would help to realize a self-powered wearable electronic system. To overcome the difficulty of wearing existing flexible film TEGs, a novel 3D fabric TEG structure is designed in this study. By using a 3D fabric as the substrate and yarns coated with thermoelectric materials as legs, a wearable and flexible TEG can be realized. The designed generator has a sandwich structure, similar to the classical inorganic generator, which allows the generation of a temperature difference in the fabric thickness direction, thus making it wearable and showing promising application in body heat conversion. To verify the effectiveness of the designed generator structure, a prototype was fabricated, using a locknit spacer fabric as the substrate and yarns coated with waterborne polyurethane/carbon nanotube thermoelectric composites as legs. The results suggest that the fabricated spacer fabric TEG prototype could work successfully, although the performance of this prototype is of a low level. To further improve the efficiency of the 3D fabric generator and apply it in wearable electronics in the future, highly efficient inorganic thermoelectric materials can be applied, and modifications on the conductive connections can be made.